Contextualisation of patient‐centred care: A comparative qualitative study of healthcare professionals' approaches to communicating with seriously ill patients about their dependent children. (7th November 2017) - Dencker, A.; Kristiansen, M.; Rix, B. A.; Bøge, P.; Tjørnhøj‐Thomsen, T.
Abstract : Patients' family relations play an important part in the provision of patient‐centred cancer care, not least when healthcare professionals encounter seriously ill patients with dependent children. Little is known about how children are perceived and dealt with in clinical encounters. In this qualitative comparative study, we explore the influence of medical contexts in three Danish hospital wards, haematology, oncological gynaecology and neuro‐intensive care, on communication with patients about their children. In exploring the degree to which the inclusion of children in clinical encounters is dependent on context, we took a comparative approach based on fieldwork in wards either exclusively focusing on cancer treatment or partially involved in critical phases of cancer treatment. We conducted 49 semi‐structured, in‐depth interviews with doctors and nurses, and 27 days of participant observation. The thematic analysis was based on Bateson's conceptualisation of communication. We found that healthcare professionals' approach to children in clinical encounters and the ways in which children were positioned on each ward were influenced by aspects specific to the ward, including the diagnosis and treatments that related specifically to the patient. Our findings suggest the need to explore further the influence of medical contexts on the inclusion of children in patient communication.